2007
DOI: 10.1097/01.jnr.0000387621.95306.98
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Women Immigrants' Life Adaptation, Social Support, and Depression

Abstract: The purpose of this study was to explore the relationships between life adaptation, social support, and depression among migrant Vietnamese women living in Meinong Township, Kaohsiung County. With a cross-sectional study design, 143 participants were recruited by purposive sampling. Structured questionnaires including Demographic Inventory Scale, Life Adaptation Scale, Social Support Scale, and Beck Depression Inventory Scale were used. Data were analyzed with Pearson's correlation and One-way ANOVA. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 10 publications
(18 reference statements)
4
26
0
Order By: Relevance
“…The present authors' results revealed a low incidence of maternal depression (0.5%) among the Vietnamese immigrant women, consistent with a previous study by Lin and Hung (), who found that the incidence of maternal depression for this cohort is 1.4%. Studies of other immigrant groups, however, revealed higher incidences of maternal depression.…”
Section: Discussionsupporting
confidence: 92%
“…The present authors' results revealed a low incidence of maternal depression (0.5%) among the Vietnamese immigrant women, consistent with a previous study by Lin and Hung (), who found that the incidence of maternal depression for this cohort is 1.4%. Studies of other immigrant groups, however, revealed higher incidences of maternal depression.…”
Section: Discussionsupporting
confidence: 92%
“…Another variable of interest that can explain the degree of social support in the immigrant population is the time spent in the host country, a phenomenon already studied by Lin and Hung [41] that support the findings of our study, that shows the longer one lives in the country of migration the more social support it has. This relationship can be explained by several circumstances: a better understanding of the host language, a better sociocultural adaptation to the new society and by the immigrants' origin.…”
Section: Discussionsupporting
confidence: 89%
“…Casado and Leung (2002) showed that Chinese American elders with language difficulties had a higher rate of depression. In the study by Lin and Hung (2007), Vietnamese female marriage immigrants in Taiwan with competent language ability had a lower rate of depression. Conflicting research results have been observed for female marriage immigrants in Korea.…”
Section: Discussionmentioning
confidence: 93%